Carol Hurney - Mays Hoopes, Laura L. (American Society for Cell Biology, 2009)
NOTE FROM THE EDITOR: Educator Highlights for CBE—Life Sciences Education show how professors at different kinds of institutions educate students in life sciences with inspiration and panache. If you have a particularly creative teaching portfolio yourself, or if you wish to nominate an inspiring colleague to be profiled, please e-mail Laura Hoopes at lhoopes@pomona.edu.